2015
DOI: 10.1186/s12917-015-0598-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclooxygenase(COX)-1 and COX-2 inhibition on furosemide-induced renal responses and isoform immunolocalization in the healthy cat kidney

Abstract: BackgroundThe role of cyclooxygenase(COX)-1 and COX-2 in the saluretic and renin-angiotensin responses to loop diuretics in the cat is unknown. We propose in vivo characterisation of isoform roles in a furosemide model by administering non-steroidal anti-inflammatory drugs (NSAIDs) with differing selectivity profiles: robenacoxib (COX-2 selective) and ketoprofen (COX-1 selective).ResultsIn this four period crossover study, we compared the effect of four treatments: placebo, robenacoxib once or twice daily and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Results obtained in the present study revealed mild alterations in the kidney function, reflected as a significant increase in urea of KT/WR-treated rats and a significant decrease in the creatinine level of both WR and KT/WR-treated groups. These altered parameters were in accordance with several reports reflecting a disturbed kidney function (Aly et al, 2015;Hörl, 2010;Kim & Joo, 2007;Pelligand et al, 2015) More recently, Lucas et al (2018) reported that NSAIDs increase the risk of developing nephrotoxicity and acute tubular necrosis and they recommended that this condition be well evaluated. The authors concluded that NSAIDs, selective and non-selective, directly interfere with renal function due to prostaglandin inhibition, and suggested acute sodium retention, which is the main cause of the overfilling effect due to arterial hypertension and edema (Chana et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Results obtained in the present study revealed mild alterations in the kidney function, reflected as a significant increase in urea of KT/WR-treated rats and a significant decrease in the creatinine level of both WR and KT/WR-treated groups. These altered parameters were in accordance with several reports reflecting a disturbed kidney function (Aly et al, 2015;Hörl, 2010;Kim & Joo, 2007;Pelligand et al, 2015) More recently, Lucas et al (2018) reported that NSAIDs increase the risk of developing nephrotoxicity and acute tubular necrosis and they recommended that this condition be well evaluated. The authors concluded that NSAIDs, selective and non-selective, directly interfere with renal function due to prostaglandin inhibition, and suggested acute sodium retention, which is the main cause of the overfilling effect due to arterial hypertension and edema (Chana et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…The epitope sequence for the CD147 antibody was proprietary, but personal communication with the manufacturer (Santa Cruz) indicated 79% homology to feline CD147. Feline intestinal goblet cells were selected as a positive control for COX-1 [ 29 ], feline kidney (macula densa) was selected as a positive control tissue for COX-2 [ 30 ] , and feline small intestine was selected as a positive control for CD147 expression [ 31 ]. For negative control purposes, primary antibodies and antiserum were replaced with control rabbit IgG (Millipore Sigma Company, Etobicoke, ON, Canada), control goat IgG, and control rabbit serum (Santa Cruz).…”
Section: Methodsmentioning
confidence: 99%
“…Positive control tissues were selected based on the published literature. Feline intestinal goblet cells were selected as a positive control for COX-1 [ 29 ], feline kidney (macula densa) was selected for COX-2 expression [ 30 ] , and feline small intestine (enterocytes) was selected as for CD147 expression [ 32 , 33 ]. Positive and negative controls were included in all of the IHC runs.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence from case-control and retrospective studies suggest that there is no correlation between a higher incidence of hyperkalemia with selective COX-2 inhibitors (the coxibs), as already described in clinical trials of the 1980s, and thus the incidence of hypokalemia with any class of NSAIDs. 4 , 9 , 14 , 17 …”
Section: Nsaids and Hydroeletrolytic Disordersmentioning
confidence: 99%
“…However, in physiological situations, such enzymes are not primary components of the hydroelectrolytic homeostasis generated in the kidneys, since the baseline production rate of prostaglandins is relatively low. 2 , 4 , 11 , 12 , 15 , 17 It has been suggested that the acute sodium retention caused by NSAIDs in healthy elderly is mediated by COX-2 inhibition, while the sudden decrease in GFR is due to COX-1 inhibition. 4 …”
Section: Nsaids and Hydroeletrolytic Disordersmentioning
confidence: 99%